FACIES ANALYSIS AND SEQUENCE STRATIGRAPHIC FRAMEWORK OF JURASSIC STRATA IN THE NACCOWLAH BLOCK, EROMANGA BASIN, AUSTRALIA - ,, MUHAMMAD IRFAN (2014)
This research presents the sequence stratigraphic framework of non-marine Jurassic succession of Naccowlah Block, Eromanga basin, Australia. The exploration and development in this basin has predominantly focused on structural traps. The main objective of this research is to provide subsurface stratigraphic framework for future exploration and field development from stratigraphic reservoir. Construction of lithostratigraphy, fluvial facies analysis, identification of depositional environment and 3rd order sequence stratigraphic application were carried out using log and core reports. It facilitated the north-south and east-west correlation and subsurface mapping to reconstruct the depositional history. The lateral distribution for the lithostratigraphy and fluvial facies were correlated, using GR, Res, and DT. Finally the main flooding surface was identified in the study area to build up system tracts in order to get sequence stratigraphic framework. The Basal Jurassic sequence contains LST and TST, deposited by meandering river and floodplain deposits. The basal unit is characterized by LST in which fluvial channel enclosed within floodplain deposits.